Another View on Soft Expert Set and Its Application in Multi-Criteria Decision-Making - Abid Khan; Muhammad Zainul Abidin; Muhammad Amad Sarwar (Mathematics)
The soft expert set (SES) is a useful mathematical tool for addressing uncertainty, with significant applications in decision-making. This study identifies some inconsistencies in the original SES framework. The study demonstrates that the majority of SES operations are in conflict with the foundational definition of an SES. Consequently, the definition of an SES is revised to not only resolve the existing complications but also enhance its applicability in real-world problems. In addition, a novel multi-criteria decision-making (MCDM) approach is proposed based on the revised SES framework, along with its concrete algorithm. The proposed algorithm is applied to a supply chain problem, and its results are compared with two existing SES-based decision-making approaches. The results reveal that the proposed algorithm offers a more precise ranking of decision alternatives and has greater applicability as compared to the other two methods. The findings of this study advance the theoretical understanding of the SES and provide a more robust tool for decision-makers in MCDM environments.